Educationg a future aged-care workforce: Shaping positive attitudes and developing collaborative practice capabilities - Cartwright, J.; Sanderson, Brooke; Whitworth, Anne; Oliver, E.; Gribble, Nigel (2015)
To deliver quality care to increasing numbers of older Australians, it is imperative that health education programs are designed to ensure graduates are equipped with the knowledge, skills, and attitudes required for employment in residential aged-care settings. An innovation is set out here that aimed to deliver a high-quality interprofessional practice placement to speech-language pathology and occupational therapy students within a residential aged-care facility, whereby students were trained to deliver a quality-of-life enrichment program, the Ashby Memory MethodTM, to residents on an individual basis. The findings of the study were positive, with students valuing the learning experience and demonstrating positive shifts in attitudes, confidence, and collaborative practice capabilities. Positive outcomes were also demonstrated for the organisation and its residents. The findings provide direction for future research and high-quality aged-care clinical placement